Konsep Memelihara Proses, Bekerja Secara Rutin, Reward dan Punishmen dalam Islam Berdasarkan Hadits - Sidik, Aditya Permana; Ilahi, Lingga Karunia; Rochaeni, Reni; Ramdhan, Dadan F (Melati Institute, 2024)
The Hadith of the Prophet Muhammad about the world as a temporary stopover provides an important lesson for Muslims not to be complacent about worldly life. This concept emphasizes that the world is not a place that straightens humans, but rather a means of tests and challenges that can be a source of reward or punishment. This study aims to understand the Islamic view of reward and punishment through the analysis of hadiths that remind humanity not to be lured by worldly pleasures because real happiness is only in the hereafter. Through a qualitative approach with a literature review of hadith sources and scholarly interpretations, this article examines how humans should direct their lives in order to get rewards in the hereafter and avoid the punishment of Allah swt..